The Role of Ranged Horses in Eco-Epidemiology of Rickettsia raoultii Infection in China - Chang, Qiao-Cheng; Hu, Yang; Wu, Ting-Ting; Ma, Xiao-Xiao; Jiang, Bao-Gui; Jia, Na; Wang, An-Qi; Jiang, Jia-Fu (Frontiers in Microbiology, 2022)
Rickettsia raoultii is a tick-borne pathogen that infects humans; however, the carriers of this pathogen have not been clearly defined. Our molecular examination of Rickettsia spp. infecting mammals and ticks in China, identified the gltA, ompA and 17KD sequences of R. raoultii in horses, raising a public health concern.